Optical Coherence Tomography Imaging After Surgical Closure of Pediatric Traumatic Macular Holes. (March 2018) - Kothari, Nikisha; Tran, Kimberly D.; Read, Sarah P.; Berrocal, Audina M.
Purpose: To date, little attention has been directed to retinal photoreceptor migration after traumatic macular hole surgical repair in the pediatric population. The purpose of this study was to evaluate optical coherence tomography (OCT) findings in the foveae of pediatric patients with history of traumatic macular hole surgical repair. Methods: Retrospective case series of 3 eyes in 3 pediatric patients with traumatic macular hole surgical repair. Spectral domain OCT images were obtained pre- and postoperatively. Results: We report 3 cases of restoration of the ellipsoid zone with good visual acuity outcomes following macular hole closure. Conclusion: Optical coherence tomography findings of an intact ellipsoid zone may be a predictor of visual acuity and explain better surgical outcomes in the pediatric population.